Fault-tolerant control of 3-phase im drive (speed-sensor fault and open-phase fault) - Jannati, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper, a fault-tolerant control strategy dedicated to star connected 3-phase Induction Motor (IM) is presented. The presented method is able to control 3-phase IM drive under healthy, speed-sensor fault and open-phase fault conditions. The proposed fault-tolerant control system is derived from an Extended Kalman Filter (to compensate speed-sensor fault) and two developed Field-Oriented Control (FOC) algorithms (to compensate open-phase fault). The performance demonstrated by the simulation results shows that, in comparison with conventional FOC, the proposed approach, provides an accurate vector control and good dynamic performance particularly in reduction of motor speed and torque oscillations.